HIV-Associated Progressive Multifocal Leukoencephalopathy: A Case Study - Elsayed Abed; Ahmed Farag El-adawey; Mohamed Hamed Rashad; Ahmed Essmat; Mohammed Ali; Ahmed Hassan Elsheshiny; Abdel-Ghaffar Fayed; Fathy Elbaz; Mahmoud Galal Ahmed; Zohreh Abna; Shaimaa Sayed Khater (Acta Medica Indonesiana, 2023)
Progressive multifocal leukoencephalopathy (PML) is a rare, life-threatening, infectious, lytic, demyelinating disease that results from reactivation of the virulent JC polyomavirus (JCV) “major opportunistic infection” in immunosuppressed individuals. We reported a case of a young girl who presented with new onset focal neurological defect, evaluated, and laboratory and radiological findings in the context of a clinical setting confirmed HIV-related-PML infection. However, remyelination does not occur, the patients may develop complications in the long term including cognitive impairment, sensory deficits, motor deficits, and disturbances in balance. We must increase our knowledge about HIV- related PML in any patient with reduced immunity and who presented with new onset neurological defect.